Геофизические исследования подводного вулканического центра вблизи юго-западной оконечности о. Симушир (Курильская островная дуга) - Блох Ю.И.; Бондаренко В.И.; Долгаль А.С.; Новикова П.Н.; Рашидов В.А.; Трусов А.А. (My University, 2014)
The paper provides results from application of designed modern computer techniques for interpretation of materials from complex geophysical investigation of submarine volcano which are located west of the south-western coast of Simushir Island in the Kurile island arc.
Keywords: 38.37.27 Петрография океанических пород и подводный вулканизм; Вулкан 6.13; Симушир; 550.83:551.214(265.53):681.3